Poisoning Effects of HCl on MOx‐WO3/TiO2 (M=Mn, Ce and V) Catalysts for Selective Catalytic Reduction of NOx by NH3. Issue 1 (20th December 2022) - Yu, Jie; Wang, Chizhong; Wang, Yazhou; Qiu, Lei; Yin, Yimeng; Li, Xing; Zhao, Feilin; Chang, Huazhen
Abstract: Selective catalytic reduction of NO x by ammonia (NH3 ‐SCR) was affected by HCl, which was widely present in industrial flue gas. In this study, the SCR performances over MO x ‐WO3 /TiO2 (MW/Ti, M=Mn, Ce and V) catalysts after HCl treatment were investigated. It was found that HCl poisoning showed inhibition and promotion in NO x conversion over MnW/Ti and CeW/Ti catalysts, respectively. While the SCR activity over VW/Ti catalyst was hardly affected by HCl. Over MnW/Ti catalyst, the rupture of the Mn−O bond by the strong Mn−Cl binding induced the formation of amorphous MnCl2 species. This Cl‐containing species with Mn in a low oxidation state exhibited poorer redox ability and NO activation, resulting in a decrease in low‐temperature SCR activity. However, instead of directly affecting the CeO x and VO x sites, gaseous HCl reacted with NH3 to form NH4 Cl species on the surface of CeW/Ti and VW/Ti catalysts. As a result, the SCR activity of VW/Ti catalyst was scarcely influenced by HCl, taking the unchanged redox ability and NH3 adsorption. With a further accumulation of NH4 Cl on CeW/Ti catalyst, the NO x conversion at low temperature was evidently enhanced due to the promotion in NO‐to‐NO2 conversion (Fast‐SCR). Abstract : Influence of Poisoning Effects on Catalytic Reduction of NOx by NH3 : HCl respectively exhibited promotion and suppression effects on the SCR activities of MnW/Ti and CeW/Ti, but had no impact on VW/Ti. For MnW/Ti−P, the inhibition of NO adsorption and activation decreased the SCR activity. Meanwhile, the promotion in "fast‐SCR" process successfully enhanced the SCR performance of CeW/Ti−P. However stable physicochemical properties maintained the NO x conversion of VW/Ti−P.